Vehicular impact resistance of seismic designed RC bridge piers. (1st October 2020) - Li, R.W.; Wu, H.; Yang, Q.T.; Wang, D.F.
Highlights: FE models of vehicle colliding with the seismic designed double-pier RC bridge are given. Failure modes of seismic designed RC pier under vehicular collisions are identified. Relationship between peak vehicular impact force and vehicular momentum is given. A new damage index for bridge pier under vehicular impact is proposed. Abstract: Bridge piers designed according to the seismic specifications are likely to be subjected to the accidental vehicular collisions during its service life cycle, while the correlations between the seismic capacity and impact resistance of bridge pier are rarely studied, as well as the practical damage evaluation approach. This paper aims to fill this research gap. Firstly, four typical double-pier RC bridges are designed based on the Chinese seismic design specifications with consideration of different seismic hazard levels, and the corresponding refined finite element models are established by using LS-DYNA. Then, based on the validated material models and numerical algorithm, the numerical simulations of total 108 vehicle-pier collision scenarios are systemically performed, including the pick-up light truck, Ford 800 medium truck and tractor-trailer heavy truck with different tonnages of 3–30 t and collision velocities of 40–120 km/h. By assessing the pier's deformation and vehicular impact force, it derives that the bridge pier designed with the enhanced seismic capacity exhibits a lower damage level and survives the higher impact speed of heavy truck, as well as withstands the successive cargo impact. Besides, five potential failure modes of the seismic designed bridge pier under vehicular collisions are identified, i.e., local damage on pier, overall collapse of bridge structure, etc. Finally, a new explicit damage index is proposed by further considering the diameter and shear-span ratio of bridge pier, then the damage levels of the vehicular impacted pier and whole bridge structure are evaluated, and the corresponding damage evaluation diagrams are given. The current work could provide helpful reference in the evaluation and design of RC bridge pier regarding both the earthquake and vehicular collisions.